Physical health and cardiometabolic risk markers among the elder people - Che Hasan, Muhammad Kamil (IIUM Press, International Islamic University Malaysia, 2017)
In Malaysia population, cardiometabolic diseases is still the leading cause of disabilities including death which cardiometabolic risks gradually rise as the age increase. The research communities particularly in clinical facing this challenge to designate the appropriate components of preventive, diagnostic including therapeutic care for the elder people in the community. Thus, by assessing the components of physical health in the elder people may provide evidence to the physiological data as complementary, and presumably may be used to foresee the elder people health status in general. The valuable effects of relationship underlying between components of physical health towards the risk for cardiometabolic risk markers in elder people, are not well understood. Thus, exploring the relationship between the components of physical health and cardiometabolic risk markers among the elder people with cardiometabolic disease was the aim of this study. The target population was healthy people and people living with cardiometabolic diseaseattending UKMMC aged 60-75. A series of test had been taken to the participants which were agility, muscular flexibility, muscular strength and cardiorespiratory endurance. They were also donated a 10ml blood sample after an overnight fast for analysis of fasting lipid profiles, high sensitivity CRP, glucose, adiponectin and insulin. The relationship of components of physical health and cardiometabolic risk markers used Spearman rho correlation for investigation. Analysis on 68 participants has been carried oResults found that there were significant positive relationship between muscular strength with blood pressure (r=0.318, p=0.008) and muscular strength with glucose (r=0.265, p=0.029). There were also significant negative relationship found between body flexibility with HOMA-IR (r=-0.291, p=0.061), body flexibility with Insulin (r=-0.276, p=0.023), body flexibility with BMI (r=- 0.289, p=0.017) and body flexibility with the circumference of the waist (r=-0.276, p=0.022). Results suggested that good health status including ideal body weight and physical fitness will lower the cardiometabolic risk markers. ut.